Projeto de cogeração: estudo de caso para aplicação em uma fábrica cafeeira - Matos, Bruno Henrique dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In recent years, business concerns have grown to reduce the costs of manufacturin g operations and to reduce the impact on the environment. This study aims at a new possibility for the thermal system already existing in a Soluble Coffee plant in order to obtain an alternative from a decentralized source of electric energy, which is feas ible and increases the reliability in the process. In this work, a case study was presented with the proposal to implement a cogeneration system. This study is in the phase of technical feasibility, in this way were made analyzes of the indicators that bes t fit the thermal electrical demands of the company, together with the best equipment that meets those needs. A backpressure steam turbine and a gas turbine will be tested for this solution, along with a recovery boiler for steam production. For the purp ose of this study, we first approached all the theoretical themes behind the thermal phenomena and concepts. Then all the energy demands of the plant and its total fuel consumption in the boilers were analyzed. To select the steam turbine, maintaining the existing steam generation performance, it was necessary to change the boilers so that the operation reached the desired pressure and temperature, 2.5MPa and 300oC respectively. In this way it was verified by the thermodynamic equations a potential for inst allation of two equipment of 1,5 MW of power. In the case of the gas assembly, a turbine of 5.7 MW of power will be installed, which will analyze the thermal energy demand of the plant, will supply this need by replacing the boiler with gas by the recovery boiler, offering a steam flow of 15 ton / hour steam, and still serving virtually all electrical demand from the plant. Finally, in order to conclude this study, we calculated the installation and operation costs of these systems, ... ( Complete abstract click electronic access below)

Nos últimos anos estão crescentes as preocupações empresárias para que se reduzam os custos das operações fabris e que se amenizem os impactos junto ao meio ambiente. Este estudo visa uma nova possibilidade ao sistema térmico já existente em uma fábrica de Café Solúvel afim de se obter uma alternativa de uma fonte descentralizada de energia elétrica, que seja viável e aumente a confiabilidade no processo. Neste trabalh o foi abordado um estudo de caso com a proposta de implementação de um sistema de cogeração. Este estudo encontra se em fase de viabilidade técnica, desta forma foram feitas analises dos indicadores que melhor se encaixam para as demandas térmicas/elétrica s da empresa, juntamente com o melhor equipamento que atenda essas necessidades. Serão testados para essa solução, uma turbina a vapor de contrapressão e uma turbina a gás, junto com uma caldeira de recuperação para produção de vapor. Para concretização de ste estudo, primeiramente foram abordados todos os temas teóricos por trás dos fenômenos e conceitos térmicos. Em seguida foram analisadas todas as demandas energéticas da planta e o seu consumo total de combustíveis nas caldeiras. Para seleção da turbina a vapor, mantendo a performance de geração de vapor já existente foi necessário a mudança das caldeiras para que a operação atingisse a pressão e temperatura desejados, 2,5MPa e 300oC respectivamente. Desta forma foi constatado pelas equações termodinâmica s um potencial para instalação de dois equipamentos de 1,5 MW de potência. No caso do conjunto a gás será instalada uma turbina de 5,7 MW de potência, que analisada a demanda de energia térmica da fábrica, irá suprir essa necessidade pela substituição da c aldeira a gás pela caldeira de recuperação, oferecendo uma vazão de vapor de ... (Resumo completo, clicar acesso eletrôninco abaixo)
Cogeneration project: case study for application in a coffee factory
Keywords: Energia eletrica e calor - Cogeração; Sistemas de energia elétrica; Caldeiras; Electric power systems